Hydrogels: Separation‐Free Polyaniline/TiO2 3D Hydrogel with High Photocatalytic Activity (Adv. Mater. Interfaces 3/2016). Issue 3 (5th February 2016) - Jiang, Wenjun; Liu, Yanfang; Wang, Jun; Zhang, Mo; Luo, Wenjiao; Zhu, Yongfa
Abstract : In article number 1500502, Y. F. Zhu and co‐workers synthesize a separation‐free polyaniline/TiO2 3D hydrogel by polymerizing conductive polymer monomer. The composite hydrogel efficiently removes organic contaminants due to the synergistic effect of adsorption‐enrichment and subsequent in‐situ photocatalytic degradation. The work provides new insights into the fabrication of hydrogel‐based nanocomposite materials and facilitates their potential application in the water purification field.